#TITLE_ALTERNATIVE# - Kusumastuti Widita (NIM 10103038), Chasanah
ABSTRACT: Nowadays, world faces a huge environmental problem i.e. air pollution due to smokestack activities. One of mathematical modeling to analyze this problem is Gaussian Plume Model (GPM) which is a steady state Gaussian-based air pollutant dispersion model. This model was developed based on diffusion equation, to evaluate pollutant concentrations from single elevated point source (e.g. stacks) in certain terrain. The pollutant to be considered is the bent-over and hot buoyant plume which dispersed continually. This model incorporates plume rise due to plume stack exit velocity and temperature. GPM is applied under varying parameters i.e. different meteorological conditions, topographical conditions, stack configurations, and pollutant characteristics. This model is represented with computer programming that created by GUI MATLAB 7, by which any user could calculate the pollutant concentrations dispersed from a stack. Furthermore, any user would obtain information about maximum concentration and its location.